266 High-Grade Glioma Arising in an Ovarian Immature Teratoma. (11th January 2018) - Kim, Grace; Estrada, Pamela; Nilforoushan, Neshat
Abstract: Primary neuroectodermal tumors of the ovary with high-grade features analogous to glioblastoma multiforme of the central nervous system are exceptionally rare. Seventeen such cases of the ovary occurring in patients 10 to 41 years of age have been previously reported. These tumors have been associated with both mature and immature teratomatous elements and gliomatosis peritonei. We report here a case of a 28-year-old (gravida 0) female patient who presented to an outside institution with abdominal pain and early satiety. A left complex adnexal mass (19.0 cm) was identified, and the patient was consented for surgery. Intraoperatively, the predominantly solid adnexal mass had signs of rupture and exophytic growth with visible peritoneal and omental implants. The contralateral ovary was enlarged with a simple cyst and otherwise unremarkable. The patient underwent left salpingo-oophorectomy, right ovarian cystectomy, omentectomy, left pelvic lymph node dissection, and optimal peritoneal tumor debulking. Within 24 days of surgery, chemotherapy with bleomycin, etoposide, and cisplatin (BEP) was initiated. Gross and microscopic evaluation confirmed a ruptured left ovarian immature teratoma with extensive mature glial tissue involving the omentum. Within the primary tumor and in association with immature pelvic implants was a component of a high-grade glioma analogous to a glioblastoma multiforme of the central nervous system. Foci of hypercellular mature glial tissue with findings of significant atypia, vascular proliferation, necrosis, greatly increased Ki67 proliferative activity, and GFAP positivity were supportive. The contralateral ovary, left fallopian tube, and left pelvic lymph nodes were free of disease. The patient is currently without evidence of disease and undergoing chemotherapy. Malignant gliomas arising in association with ovarian teratomas are exceptionally rare and are thus poorly studied. Treatment modalities formerly utilized are variable. Patients generally fare poorly, and prognosis is largely dependent on conventional tumor grade and staging.